A simple method to construct a low-cost immunosensor based on a dithiol-functionalized polydopamine platform. (15th February 2021) - Liu, Bo; Yang, Luanying; Wang, Gang; He, Sha; Wang, Xiaobo; Ye, Ling
Abstract : A simple and low-cost electrochemical CEA immunosensor was investigated via the self-polymerization of dopamine and a dithiol compound spacer for the covalent immobilization of antibodies. The designed CEA immunosensor exhibited a linear response and a low detection limit. Abstract : In this study, a simple and low-cost electrochemical immunosensor for the detection of tumor markers (carcinoembryonic antigen, CEA, as a model) was investigated. The self-polymerization of dopamine was used to provide a secondary reaction platform, and a more stable dithiol compound (thioctic acid) as a spacer was fixed on the platform via the Michael's addition reaction. A dithiol-functionalized platform was used for the covalent immobilization of antibodies, and the structure showed significant changes in the atomic force microscopy (AFM) and X-ray photoelectron spectroscopy (XPS) images. The electrochemical impedance spectroscopy (EIS) and differential pulse voltammetry (DPV) measurements were performed to test the performance of a double-antibody sandwich structure. The designed CEA immunosensor exhibited a linear response over a concentration range of 0.05–80 ng mL −1 with a low detection limit of 1.21 pg mL −1, and the results demonstrated a potential application for clinical diagnosis.